Inaugural lecture : leveraging research & innovation in ICTs for Socio-Economic Development in Malaysia - Yeo, Alvin Wee (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Universiti Malaysia Sarawak (UNIMAS) has been involved in ICT for Rural Development research projects since 1999, starting with eBario, a telecentre implemented to provide equal access to information and communications technologies (ICTs) to a rural and remote community, in Malaysian Borneo. Employing a holistic, multi-sectorial, multi-disciplinary and participatory approach, eBario has delivered significant socio-economic changes to the Kelabits, an indigenous group living in Bario. The eBario model has been replicated to four other indigenous communities, also in remote and rural locations in East Malaysia, as well as to four other Orang Asli sites in West Malaysia. Two of the exemplary projects, eBario and eLamai, demonstrate the ripple effects of the participatory approach in generating diverse research and innovation opportunities in areas of anthropology, renewable energy, indigenous knowledge conservation, indigenous tourism, and handicraft making. These projects, implemented by the Institute of Social Informatics and Technological Innovations, UNIMAS, demonstrate how research and innovation in ICT for development projects can create pathways to academic and socio-economic impacts as well as shape policies which govern the deployment of ICTs to underserved communities in Malaysia.